TAXES IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Saifullah (Jurnal Penelitian Progresif, 2022)
According to Islamic Fiqh, taxes are mandatory alms that the government levies on citizens for the benefit and prosperity of the people. As for Law No. 28 of 2007, article 1, tax is a mandatory contribution to the state that is owed by an individual or entity that is coercive based on the law without receiving direct compensation and is used for state needs for the greatest prosperity of the people. Taxes have very significant educational values ​​in various aspects, both from religious, legal, economic, practical application and development aspects.